The use of a locally isolated yeast in the expression of recombinant W200R protease - Abdul Razak, Fatin Syuhada (2015)
Yeasts are well-received industrial hosts for the production of recombinant protein due to efficient expression. The thermostable F1 protease contained the mutation of tryptophan at residue 200, substituting arginine (W200R). The gene then was cloned into Pichia pastoris commercial yeast system. However, the production of W200R protease was low (38.71 U/mL) while the optimal incubation time for expression was recorded at 48h. Meanwhile, a newly isolated yeast, Pichia sp. strain SO, bearing 99% of similarity with Pichia guillermondii has been screened for protease activity and no thermostable protease was found. Hence, the recombinant mutated W200R protease gene was transformed into a new host, Pichia sp. SO through electroporation method with pPICZαB as the vector, similar to Pichia pastoris expression vector. Following this, seven colonies were screened for protease activity whereby colony R3 exhibited the highest protease secretion. R3 was selected for optimization which includes methanol induction and time course study. In the end, the cultivation of recombinant R3 in yeast peptone tryptic methanol (YPTM) medium supplemented with 2.5% (v/v) methanol demonstrated alleviated protease productivity with 100% relative activity after 18 hours of post induction. In conclusion, this study has shown that isolate SO is a promising host to express W200R protease and gain new insights for the development of a local yeast for the expression of heterologous recombinant protein.